Compressed Sensing: Theory and Applications - Yonina C. Eldar, Gitta Kutyniok (Cambridge Cambridge University Press, 2014)
School of Mathematics and Natural Sciences
MIR No: 165
Order Date: 2024-07-08
Order No: CU/OPEX/LIBRARY/24/2024-25
Received Date: 2024-09-20
Keywords: Communications engineering